Model Pelaksanaan Putusan Mahkamah Konstitusi yang Eksekutabilitas Dalam Pengujian Peraturan Perundang-Undangan di Indonesia - I Gusti Ayu Ketut Rachmi Handayani; Lego Karjoko; Abdul Kadir Jaelani (Administrative Law Departement Faculty of Law Universitas Sebelas Mare, 2019)
This research is motivated by the number of unimplemented Constitutional Court decisions, although the nature of the Constitutional Court 's rulings is final and binding. This form of work is ethical normative. That investigation is descriptive. The data type used is the secondary data. Secondary techniques for the processing of data were obtained through library work. Primary and secondary data were qualitatively analysed. The results of the study show that, first, the decision of the Constitutional Court, which is not implementing the compilation of its decision, does not include a time limit for its implementation, while the decision of the Constitutional Court, which contains a grace period, is quickly followed through the establishment of an invitation regulation. Second , the model of the future functional decision of the Constitutional Court is the decision of the Constitutional Court which contains a period of grace and the institutionalization by constitutional permit of constitutional questions. Keywords: Constitutional Court, time of grace and Issue of the Constitution.